Effect of Carbon Ion Radiation Induces Bystander Effect on Metastasis of A549 Cells and Metabonomic Correlation Analysis - Yang, Zhen; Zhang, Qiuning; Luo, Hongtao; Shao, Lihua; Liu, Ruifeng; Kong, Yarong; Zhao, Xueshan; Geng, Yichao; Li, Chengcheng; Wang, Xiaohu (Frontiers in Oncology, 2021)
Objective To analyze the effect of carbon ion (12C6+) radiation may induce bystander effect on A549 cell metastasis and metabonomics. Methods A549 cell was irradiated with carbon ion to establish the clone survival model and the transwell matrix assay was applied to measure the effect of carbon ion on cell viability, migration, and invasion, respectively. Normal human embryonic lung fibroblasts (WI-38) were irradiated with carbon ions of 0 and 2 Gy and then transferred to A549 cell co-culture medium for 24 h. The migration and invasion of A549 cells were detected by the Transwell chamber. The analysis of metabonomic information in transfer medium by liquid phase mass spectrometry (LC-MS), The differential molecules were obtained by principal pomponent analysis (PCA) and the target proteins of significant differences (p = 1.7 × 10−3) obtained by combining with the STICH database. KEGG pathway was used to analyze the enrichment of the target protein pathway. Results Compared with 0 Gy, the colony formation, migration, and invasion of A549 cells were significantly inhibited by carbon ion 2 and 4 Gy irradiation, while the inhibitory effect was not significant after 1 Gy irradiation. Compared with 0 Gy, the culture medium 24 h after carbon ion 2 Gy irradiation significantly inhibited the metastasis of tumor cells (p = 0.03). LC-MS analysis showed that 23 differential metabolites were obtained in the cell culture medium 24 h after carbon ion 0 and 2 Gy irradiation (9 up-regulated and 14 down-regulated). Among them, two were up-regulated and two down-regulated (p = 2.9 × 10−3). 41 target proteins were corresponding to these four differential molecules. Through the analysis of the KEGG signal pathway, it was found that these target molecules were mainly enriched in purine metabolism, tyrosine metabolism, cysteine and methionine metabolism, peroxisome, and carbon metabolism. Neuroactive ligand-receptor interaction, calcium signaling pathway, arachidonic acid metabolism, and Fc epsilon RI signaling pathway. Conclusion The bystander effect induced by 2 Gy carbon ion radiation inhibits the metastasis of tumor cells, which indicates that carbon ions may change the metabolites of irradiated cells, so that it may indirectly affect the metabolism of tumor cell growth microenvironment, thus inhibiting the metastasis of malignant tumor cells.